Divergent effects of resistance training and anabolic steroid on the postsynaptic region of different skeletal muscles of aged rats - Krause Neto, Walter; Silva, Wellington de Assis; Ciena, Adriano Polican [UNESP]; Anaruma, Carlos Alberto [UNESP]; Gama, Eliane Florencio (Elsevier B.V., 2017)
This study aimed to analyze the effects of resistance training associated with testosterone administration in the neuromuscular junction (NMJ) postsynaptic region of different skeletal muscle types of aged rats. Wistar rats were divided into: SEI - 20-months-old control, SEF - 24-months-old control, T - 20-months-old with testosterone, S - 20-months-old resistance trained and ST - 20-months-old with resistance training associated with testosterone propionate. All groups were submitted to familiarization and maximum load carrying testing (MLCT). The MLCT was applied before and after the resistance training (RT) period. RT (6-8x/session with progressive loads of 50 to 100%, 3x/week and 120 s interval) was performed in ladder climbing for 15 weeks. The administration of testosterone propionate was performed 2x/week (10 mg/kg/body weight). After euthanize, soleus and plantaris muscles were removed and prepared for histochemistry and cytofluorescence. T, S and ST significantly increased their maximum carrying load capacity compared to SEI and SEF (p < 0.05). For soleus postsynaptic region, ST had lower total and stained area than SEF (p < 0.05). For plantaris, the postsynaptic component of T was statistically larger than SEI (p < 0.05). For soleus histochemistry, T, S and ST groups showed the same magnitude of type I myofibers hypertrophy, thus statistically different from SEI and SEF (p < 0.05). The cross-sectional area of the type IIa myofibers of the ST was larger than SEF (p < 0.05). The volume density of type I myofibers show to be lower in ST than SEI (p < 0.05). As for type IIa myofibers, ST increased Vv [type IIa] compared to SEI and SEF (p < 0.05). For plantaris, T significantly hypertrophied type I myofibers compared to SEI and SEF (p < 0.05). S and ST demonstrated significant increases of type I myofibers compared to SEI and SEF (p < 0.05). As for type IIx myofibers, both S and ST showed myofibers larger than SEI (p < 0.05). However, only the ST had significant difference compared to SEF (p < 0.05). In conclusion, both therapies, alone or combined, have little effect on the morphology of the NMJ postsynaptic region of distinct muscles. Moreover, the three therapies are potentially stimulating for strength gains and muscle hypertrophy.
Keywords: Strength training; Aging; Neuromuscular junction; Acetylcholine receptors; Peripheral nervous system